IGBO APPRENTICESHIP MODEL AND ENTREPRENEURSHIP DEVELOPMENT IN ABIA STATE - Ndidiamaka Emeh, (PEOPLE: International Journal of Social Sciences, 2025)
The study examined the effect of the Igbo apprenticeship model on Entrepreneurship Development in Abia state. The specific objectives were to; examine the effect of skills acquisition on entrepreneurship development and evaluate the effect of training on entrepreneurship development in Abia state. A descriptive research design was adopted for the study. A questionnaire design with a 4-point Likert scale was used to collect data. Using the Statistical Package for Social Sciences, both descriptive and inferential statistics were applied to the acquired data (SPSS 28.0). Analysis was conducted using simple linear regression analysis. The result revealed that Skills acquisition has a significant effect on entrepreneurship development with a value of (F = 29.618; p = 0.002), and also, Training had a significant effect on entrepreneurship development with avalue of (F = 21.371; p = 0.003) in Abia state. The study concluded that the Igbo apprenticeship model had a significant and positive effect on entrepreneurship development in Abia State. The study recommended that the government and relevant agencies should recognize and provide institutional support to the Igbo apprenticeship model.